Emosi, Moral dan Nilai Karakter Novel Padang Bulan Karya Andrea Hirata - -, Khoirunnisa Dwi Astuti (Educreative : Jurnal Pendidikan Kreativitas Anak, 2021)
The purpose of research is (1) to describe and describe the class of the main character in Andrea hirata’s Padang Bulan novel, (2) describe and describe the moral character of the lead character in Andrea hirata, (3) describe and explain the value of character education and relevance in Andrea hirata’s Padang Bulan novel. It is kind of qualitative study with content analysis and with an approach to literary psychology. The object of this research is Andrea hirata’s Padang Bulan novel. Data obtained is analyzed with qualitative descriptive techniques. The emotional development on the protagonist named Enong in a prairie novel based on love or affection in fear and sadness. The result includes a (1) person’s emotional development in a Padang Bulan novel based on the findings of love or affection, fear and sadness. (2) The moral development of the character in Andrea hirata’s prairie novel is that the religious, esteem has a death-fear, fear of loneliness and a strong friendship with friend’s and family. The value of karakter education and relevance contained in Andre hirata’s Padang Bulan novel the religious independent hard work of the democratic collegiate discipline of creationism and nationalistic fervor.